2022
DOI: 10.1159/000526382
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Parental Perspectives of the Social and Educational Needs for Expanding Newborn Screening through Genomic Sequencing

Abstract: <b><i>Objective:</i></b> The aim of this study was to explore the parental views, attitudes, and preferences of expanded newborn screening (NBS) through genomic sequencing. <b><i>Study Design:</i></b> We conducted a semi-structured interview study with English and Spanish speaking mothers who had given birth within the USA in the past 5 years. The interviews explored opinions of expanding NBS, ethical and privacy concerns, and educational and social needs. <b&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Because each clinical area included a different number of genes, we also tabulated the percentage of gene-disease pairs per area endorsed by experts. The highest percentage of genes that reached 80% or higher concordance were related to metabolic disorders (25…”
Section: Expert Concordance For Gene-disease Associationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because each clinical area included a different number of genes, we also tabulated the percentage of gene-disease pairs per area endorsed by experts. The highest percentage of genes that reached 80% or higher concordance were related to metabolic disorders (25…”
Section: Expert Concordance For Gene-disease Associationsmentioning
confidence: 99%
“…Lack of data regarding downstream medical, psychosocial, and economic effects of NBSeq, however, has contributed to concerns regarding its feasibility, cost, clinical utility, and associations with patient autonomy, privacy, and distress. 6,8,[13][14][15][16][17][18][19][20][21] Studies have indicated that a high proportion of individuals, particularly parents, are interested in expanding the number of disorders included in newborn screening, [22][23][24][25] including through NBSeq. [26][27][28][29][30] Surveys of pediatricians 31 and genetic counselors 32 have revealed more nuanced perspectives but still largely positive attitudes toward NBSeq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 34 groups worldwide are exploring genomic sequencing as a way to expand newborn screening and identify children at high risk for hundreds of actionable genetic disorders. 1 Stakeholders, including diverse groups of parents, 2,3 rare disease specialists, 4 primary care physicians, 5 genetic counselors, 4,6 and the public 7 support the implementation of genomic newborn screening for at least some genetic disorders. However, many clinical, ethical, and technological barriers to implementation remain.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst some of these issues have been explored in health systems with large private health insurance funding models, namely in North America (25)(26)(27), there is paucity of research on stakeholder perspectives of genomic NBS within health domains that are predominantly publicly funded, cover wide geographical expanses characteristic of the Australasian region, and encompass socio-demographically heterogenous (including Indigenous) populations. In Australia, while there has been a degree of systematic synthesis of information on genomic NBS from the perspective of the lay public (26,28), and from rare disease medical experts (29,30), the attitudes of parents of children with heterogenous genetic conditions (diagnosed with and without NBS) have not been analysed, nor have the unique challenges faced by policy makers when considering whether and how to incorporate genomics into NBS (31).…”
Section: Introductionmentioning
confidence: 99%